2008
DOI: 10.1073/pnas.0711074105
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of ryanodine receptor complex causes “leaky” channels: A molecular mechanism for decreased exercise capacity

Abstract: During exercise, defects in calcium (Ca 2؉ ) release have been proposed to impair muscle function. Here, we show that during exercise in mice and humans, the major Ca 2؉ release channel required for excitationcontraction coupling (ECC) in skeletal muscle, the ryanodine receptor (RyR1), is progressively PKA-hyperphosphorylated, S-nitrosylated, and depleted of the phosphodiesterase PDE4D3 and the RyR1 stabilizing subunit calstabin1 (FKBP12), resulting in ''leaky'' channels that cause decreased exercise tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
327
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 295 publications
(340 citation statements)
references
References 28 publications
9
327
0
4
Order By: Relevance
“…Bellinger et al (2008) observed that depletion of both PDE4D3 and FKBP12 led to impaired exercise performance. Exercise led to a progressive increase in RyR1 nitrosylation that was thought to promote FKBP12 disassociation, correlating well with expected increases in nNOSμ expression and activity.…”
Section: Mechanisms By Which Nnos Splice Variants Regulate Skeletal Mmentioning
confidence: 99%
See 4 more Smart Citations
“…Bellinger et al (2008) observed that depletion of both PDE4D3 and FKBP12 led to impaired exercise performance. Exercise led to a progressive increase in RyR1 nitrosylation that was thought to promote FKBP12 disassociation, correlating well with expected increases in nNOSμ expression and activity.…”
Section: Mechanisms By Which Nnos Splice Variants Regulate Skeletal Mmentioning
confidence: 99%
“…The cytoplasmic amino terminus of RyR1 acts as a scaffold for regulatory proteins such as calstabin1, also known as FK506 binding protein 12 (FKBP12) (Kushnir et al 2010). FKBP12 is required for normal exercise performance and is thought to stabilize RyR1 by increasing its closed state probability, thereby preventing "Ca 2+ leak" (Bellinger et al 2008). Pathogenic RyR1 Ca 2+ release or a "Ca 2+ leak" can lead to global perturbation of muscle Ca 2+ handling, including depletion of SR Ca 2+ stores and muscle damage and fatigue (Wang et al 2005;Bellinger et al 2008, Figure 1).…”
Section: Mechanisms By Which Nnos Splice Variants Regulate Skeletal Mmentioning
confidence: 99%
See 3 more Smart Citations